Spiroplasma as facultative bacterial symbionts of stinkbugs - Kakizawa, Shigeyuki; Hosokawa, Takahiro; Oguchi, Kohei; Miyakoshi, Kaori; Fukatsu, Takema (Frontiers in Microbiology, 2022)
Many insects are associated with facultative symbiotic bacteria, and their infection prevalence provides an important clue to understand the biological impact of such microbial associates. Here we surveyed diverse stinkbugs representing 13 families, 69 genera, 97 species and 468 individuals for Spiroplasma infection. Diagnostic PCR detection revealed that 4 families (30.8%), 7 genera (10.1%), 11 species (11.3%) and 21 individuals (4.5%) were Spiroplasma positive. All the 21 stinkbug samples with Spiroplasma infection were subjected to PCR amplification and sequencing of Spiroplasma’s 16S rRNA gene. Molecular phylogenetic analysis uncovered that the stinkbug-associated Spiroplasma symbionts were placed in three distinct clades in the Spiroplasmataceae, highlighting multiple evolutionary origins of the stinkbug-Spiroplasma associations. The Spiroplasma phylogeny did not reflect the host stinkbug phylogeny, indicating the absence of host-symbiont co-speciation. On the other hand, the Spiroplasma symbionts associated with the same stinkbug family tended to be related to each other, suggesting the possibility of certain levels of host-symbiont specificity and/or ecological symbiont sharing. Amplicon sequencing analysis targeting bacterial 16S rRNA gene, FISH visualization of the symbiotic bacteria, and rearing experiments of the host stinkbugs uncovered that the Spiroplasma symbionts are generally much less abundant in comparison with the primary gut symbiotic bacteria, localized to various tissues and organs at relatively low densities, and vertically transmitted to the offspring. On the basis of these results, we conclude that the Spiroplasma symbionts are, in general, facultative bacterial associates of low infection prevalence that are not essential but rather commensalistic for the host stinkbugs, like the Spiroplasma symbionts of fruit flies and aphids, although their impact on the host phenotypes should be evaluated in future studies.